Exposure to air pollution and development of asthma and rhinoconjunctivitis throughout childhood and adolescence: a population-based birth cohort study. Issue 12 (December 2015) - Gehring, Ulrike; Wijga, Alet H; Hoek, Gerard; Bellander, Tom; Berdel, Dietrich; Brüske, Irene; Fuertes, Elaine; Gruzieva, Olena; Heinrich, Joachim; Hoffmann, Barbara; de Jongste, Johan C; Klümper, Claudia; et al.
Summary: Background: Previous published analyses have focused on the effect of air pollution on asthma and rhinoconjunctivitis throughout early and middle childhood. However, the role of exposure to air pollution in the development of childhood and adolescent asthma and rhinoconjunctivitis remains unclear. We aimed to assess the longitudinal associations between exposure to air pollution and development of asthma and rhinoconjunctivitis throughout childhood and adolescence. Methods: We did a population-based birth cohort study of 14 126 participants from four prospective birth cohort studies from Germany, Sweden, and the Netherlands with 14–16 years of follow-up. We linked repeated questionnaire reports of asthma and rhinoconjunctivitis with annual average air pollution concentrations (nitrogen dioxide [NO2 ], particulate matter [PM] with a diameter of less than 2·5 μm [PM2·5 ], less than 10 μm [PM10 ], and between 2·5 μm and 10 μm [PMcoarse ], and PM2·5 absorbance [indicator of soot]) at the participants' home addresses. We analysed longitudinal associations of air pollution exposure at participants' birth addresses and addresses at the time of follow-up with asthma and rhinoconjunctivitis incidence and prevalence in cohort-specific analyses, with subsequent meta-analysis and pooled analyses. Findings: Overall, the risk of incident asthma up to age 14–16 years increased with increasing exposure to NO2 (adjusted meta-analysis odds ratio [OR] 1·13 per 10 μg/m 3 [95% CI 1·02–1·25]) and PM2·5 absorbance (1·29 per 1 unit [1·00–1·66]) at the birth address. A similar, albeit non-significant, trend was shown for PM2·5 and incident asthma (meta-analysis OR 1·25 per 5 μg/m 3 [95% CI 0·94–1·66]). These associations with asthma were more consistent after age 4 years than before that age. There was no indication of an adverse effect of air pollution on rhinoconjunctivitis. Interpretation: Exposure to air pollution early in life might contribute to the development of asthma throughout childhood and adolescence, particularly after age 4 years, when asthma can be more reliably diagnosed. Reductions in levels of air pollution could help to prevent the development of asthma in children. Funding: The European Union.